PRINCIPLES OF THE APPLICATION OF CORPUS ANALYSIS IN INCLUSIVE EDUCATION - Fayzieva Malikajon Choshovna (Bright Mind Publishing, 2025)
This paper looks into core ideas behind using corpus analysis within inclusive education, pulling insights from key researchers including Bukvic (2014), Loguercio (2018), Barber (2018), Crawford (2020), and Keppens et al. (2021). Because of their work in inclusive teaching methods and language studies based on corpora, this research gathers recent results while combining them into one connected model for using corpus tools across varied learning environments. It shows how data-based learning boosts vocabulary skills, encourages independent learners, while also helping tailor teaching for those with special needs. Focus shifts toward access, flexibility, alongside ethical issues when building and using corpora. The analysis proves corpus methods, if matched with inclusion goals, can boost both impact and fairness in EFL teaching - supporting diverse language use along with inclusive classroom strategies.
Keywords: Corpus analysis, inclusive education, data-driven learning, lexical competence, accessibility, differentiated instruction.